ANALISIS RENTABILITAS USAHA PETERNAKAN AYAM RAS PETELUR UD. TETEY PERMAI DI KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Ngantung, Indri F; Makalew, A F; Panelewen, V V.J; Lumenta, I D.R (ZOOTEC, 2019)
ABSTRACT ANALYSIS OF THE RENTABILITY LAYING CHICKEN HUSBANDRY BUSINESS FARM UD.  TETEY PERMAI IN DIMEMBE DISTRICT OF MINAHASA UTARA REGENCY.The purpose of this study was to determine whether the laying chicken business of UD. Tetey Permai profitable or not. This study was carried out in laying chicken business UD. Tetey Permai in Dimembe District, North Minahasa regency on December 21, 2017 to January 31, 2018. Data collection is done through direct interviews using a questionnaire to the owners of farm companies and animal husbandry managers. The data taken is primary data and secondary data. Primary data is obtained directly from the management of UD Tetey Permai, secondary data is data obtained through government agencies related to research, namely District office and office of the Department Agriculture and Animal Husbandry. The data analysis model used is the analysis of rentability. Based on the results of the study it was known that the laying chicken business UD. Tetey Permai has been profitable. This is indicated by the value rentability (R) of 34% wich exceeds the BNI’s bank deposit rate of 6.25%. Keywords : Laying Chicken, Rentability